Controllable Orientation of MoSe2 Nanosheets Anchored on Carbon Cloth as Self-Supporting Anodes for Improved Sodium Storage Performance. Issue 2 (3rd February 2020) - Xu, Peiguang; Cao, Liyun; Li, Jiayin; Ma, Dingying; Guo, Ling; Chen, Shaoyi; Huang, Jianfeng
Abstract : It is an important strategy to improve the sodium storage performance by using carbon cloth to support the active material. However, the effect of structural changes of active materials anchored on the surface of carbon cloth on sodium storage performance remains to be further studied. In this work, we control MoSe2 morphology on the surface of carbon cloth via annealing conditions. Under different annealing conditions, MoSe2 shows vertical, tilted and horizontal morphology on the surface of carbon cloth. When used as anode materials for sodium ion storage, the tilted-orientation MoSe2 composite electrode shows the best sodium storage performance, achieving a high cycling capacity of 253 mA h g −1 after 200 cycles at 1 A g −1 and excellent rate performance of 140.5 mA h g −1 at 5.0 A g −1 . The excellent performance is related to the orientation of MoSe2 on carbon cloth. The tilted-orientation MoSe2 /CC(carbon cloth) has hierarchical two-dimensional nanosheets structure and strong interface contact, which can prevent the self-aggregation of active material and keep well contact between MoSe2 nanosheets with carbon cloth. This work provides a reference to improve sodium storage performance for two-dimensional layered transition-metal dichalcogenides.